Dynamic observation and qualitative analysis of a psychological crisis hotline during the COVID-19 pandemic - Ouyang, Mengyuan; Song, Shasha; Ma, Hui; Yang, Hua; Leng, Jing; Zhou, Ping; Teng, Changjun; Ou, Hongxia; Li, Jijun; Liu, Na; Zhang, Ning (Frontiers in Health Services, 2022)
Objective: To analyze the chief complaints of psychological crisis hotlines during the COVID-19 epidemic in Jiangsu China, and to summarize the psychological characteristics of the public during the different stages of COVID-19. Methods: The chief complaints of calls to the psychological crisis hotline between January 27, 2020 to June 30, 2020. 578 were extracted and grouped using thematic analysis into categories. After statistical analysis, the monthly and three-period trends were observed dynamically to determine if there were statistical differences in the proportion of specific chief complaints over the phases. Results: There were a total of 495 cases of psychological problems or physical discomfort, accounting for 85.64% of the total sample number of hotline calls related to the epidemic. The numbers of callers with anxiety, depression, obsessive-compulsive symptoms, illness anxiety, insomnia and physical discomfort were 370 (64.01%), 103 (17.99%), 33 (5.71%), 36 (6.23%), 51 (8.82%) and 72 (12.46%), respectively, and 83 (14.36%) callers consulted other problems. The monthly main complaints showed a fluctuating trend, and each main com-plaint peaked at different stages. The main complaints during the three stages had distinct features respectively, and the proportions of calls for the specific complaints differed statistically over the phases. Conclusion: Dynamic observation and qualitative analysis of psychological crisis hotline data might indicate dynamic changes and accordingly provide guidance for online crisis intervention when other public health crises occur.